Tidal distortion caused by the resonance of sexta‐diurnal tides in a micromesotidal embayment. Issue 10 (18th October 2016) - Song, Dehai; Yan, Yuhan; Wu, Wen; Diao, Xiliang; Ding, Yang; Bao, Xianwen
Abstract: Double high water and double‐peak flood current were observed in Daya Bay (DYB), China, which is a shallow, mixed, mainly semidiurnal‐tide dominated bay with a micro to mesotidal range. Harmonic analysis reveals that the quarter and especially the sexta‐diurnal constituents are getting much stronger as tides propagating into the bay. The astronomical tides‐induced tidal asymmetry is yet dominant at the bay entrance but overtaken by the sexta‐diurnal tides at the end of the bay. Both the M4 and M6 tide meet the requirement proposed in previous studies but still unable to produce a double high water alone. Therefore, the conditions to produce a double high water between a fundamental tide and its higher harmonics need to be revisited. Analytical solutions were obtained in this paper, which fit the numerical solutions very well. Modeling result indicates M6 alone with M2 can produce the double high water in DYB but limited in some regions, while the combination of M2, M4, and M6 tides would enhance the capability. The amplification of sexta‐diurnal tides in DYB is dominated by resonance and followed by shoaling effect. Bottom friction damped M6 a lot and largely confined its amplification. However, the quadratic friction and other nonlinear processes are just responsible for about 10% of the total M6 increase. Key Points: Notable amplification of sexta‐diurnal tides alters tidal dynamic system in a micromesotidal embayment Conditions to produce double high waters by a fundamental tide and its higher harmonics are revisited analytically Resonant response of sexta‐diurnal tides can be extended from embayment to continental shelf